Pengaruh Persepsi Dan Motivasi Mahasiswa Akuntansi Terhadap Minat Mengikuti “Kampus Merdeka” Dengan Pemahaman Akuntansi Sebagai Variabel Intervening - Elizabeth Simatupang; Indrawati Indrawati Yuhertiana (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to examine the effect of perceptions and motivation of accounting students on their interest in participating in an “independent campus” with an understanding of accounting as an intervening variable. The sample used in this study amounted to 55 accounting students class 2017-2018 who have participated in an independent campus. The data used in this study are primary data obtained through direct distribution of questionnaires to accounting students. The data analysis technique in this study used SmartPLS 2.0 for windows. The results in this study indicate that student perceptions, motivation is a significant influence on student interest in joining an independent campus with an understanding of accounting.